The Viewpoints of Indonesian Pupils Regarding ELT in Shadow Education - Zuana, Muhammad Mujtaba Mitra (Majapahit Journal of English Studies, 2024)
The escalating demand for shadow education in Indonesia gives rise to concerns regarding the calibre of instruction provided in institutions. Therefore, the purpose of this research is to compare how students perceive English language instruction in institutions and shadow education. This research employs semi-structured individual interviews as a methodological approach to gather comprehensive data regarding the experiences and perceptions of students. Students at the secondary level who possessed substantial experience with the English shadow education program comprised the participants. Students' perceptions of shadow teaching encompassed a variety of facets, including instructional materials, learning outcomes, instructional activities, instructors' instructional performance, and educational media, according to this study. In practical terms, the student's viewpoint regarding shadow education was predominantly favorable. Moreover, in light of the findings of this research, policymakers and education authorities must consider curricular and methodological reforms immediately to improve the efficacy of English instruction and the academic achievements of pupils following their preferences, needs, and concerns regarding shadow teaching.